Substrate Characterization and Outcomes of Ventricular Tachycardia Ablation in TTN (Titin) Cardiomyopathy: A Multicenter Study. (28th July 2021) - Enriquez, Andres; Liang, Jackson; Smietana, Jeffrey; Muser, Daniele; Salazar, Pablo; Shah, Rajan; Badhwar, Nitish; Bogun, Frank; Marchlinski, Francis; Garcia, Fermin; Baranchuk, Adrian; Tung, Roderick; et al.
Abstract : Background: Truncating variants of the TTN ( titin ) gene are a leading cause of dilated cardiomyopathy and have been associated with an increased risk of ventricular arrhythmias. This study evaluated the substrate distribution and the acute and long-term outcomes of patients with TTN -related cardiomyopathy undergoing ventricular tachycardia (VT) ablation. Methods: This multicenter registry included 15 patients with dilated cardiomyopathy (age, 59±11 years; 93% men; ejection fraction, 30±12%) and genotypically confirmed truncating variants of the TTN gene who underwent VT ablation between July 2014 and 2020. Results: All patients presented with sustained monomorphic VT, including electrical storm in 4 of them. A median of 2 VTs per patient were induced during the procedure (cycle length, 318±68 ms), and the predominant morphologies were left bundle branch block with inferior axis (39%) and right bundle branch block with inferior axis (29%). A complete map of the left ventricle was created in 12 patients and showed voltage abnormalities mainly at the periaortic (92%) and basal septal regions (58%). A preprocedural cardiac magnetic resonance imaging was available in 13 patients, and in 11, there was evidence of left ventricular delayed gadolinium enhancement, with predominantly midmyocardial distribution. Sequential ablation from both sides of the septum was required in 47% of patients to target septal intramural substrate, and epicardial ablation was performed in 20%. At the end of the procedure, the clinical VT was noninducible in all patients, while in 3 cases, a nonclinical VT was still inducible. After a follow-up of 26.5±23.0 months, 53% of patients experienced VT recurrence, 20% received transplant or mechanical circulatory support, and 7% died. Conclusions: The arrhythmogenic substrate in TTN -related cardiomyopathy involves the basal septal and perivalvular regions. Long-term outcomes of catheter ablation are modest, with high recurrence rate, likely related to an intramural location of VT circuits.